PENERAPAN MODEL PEMBELAJARAN LEARNING CYCLE UNTUK MENINGKATKAN HASIL BELAJAR IPA SISWA KELAS VA SD NEGERI 181 PEKANBARU - Suryana '; Mahmud Alpusari; Lazim N (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2016)
Abstract : This research aims to improve the achievement science of school year 2015/2016. The subjects of the research was the students class VA of SDN 181 Pekanbaru in number 44 students. It is a classroom research by two cycles. The data of the research shows that the achiement having improved. It is proven by the score result of the theacher’s activity on the cycle I by mean 60% (enough category) improved as 10% to 70% (good category) and cycle II 80% (good category) improved as 5 % to 85% (very good category). The students activity on the cycle I by mean 60% (enough category) improved as 5% to 65% (good category) and the cycle II improved by mean 75% (good category) improved as 10% to 85% (very good category). The research finding also having improved, where before the learning cycle learning model. Was implemented on the passed based score was 18 students (40,90%) by mean 62,20. The cycle I, the passed students having improved as 28 students (63,64%) by mean 78,55 and on the cycle II improved to be 37 students (84,09%) by mean 83,64, this show that the application of learning learning cycle model can improve science learning outcomes grader VA SD Negeri 181 PekanbaruKeywords: Learning Cycle Model, achievement